Feeding ecology of the Burrowing Owl Athene cunicularia punensis (Strigiformes: Strigidae) in the Jambelí archipelago, El Oro province, southwestern Ecuador - Orihuela Torres, Adrian (2018)
The diet of Burrowing Owl (Athene cunicularia punensis) was studied in four territories in the Jambelí archipelago, El Oro, southwestern Ecuador, from November 2015 to April 2016, collecting 182 pellets. Arthropods were the main prey group in frequency of occurrence (86.5%), followed by mammals (12%) and birds (1.5%), but mammals (Mus musculus and Rattus rattus) contributed 58.5% of the biomass, arthropods 33.2% and birds 8.2%. No significant differences were found in the diet among the four pairs studied. Our study confirmed the important role of Athene cunicularia as predator of pests like introduced rodents and potentially harmful arthropods.